A stakeholder view of critical success factors for biogas-electricity implementation at cattle farms in Malaysia / Shahrul Suhaimi Ab Shokor, Zurina Ismail and Jegatheesan Rajadurai - Ab Shokor, Shahrul Suhaimi; Ismail, Zurina; Rajadurai, Jegatheesan (UiTM Cawangan Johor, 2019)
Malaysia has great potential for biogas production from cattle manure waste. According to the Department of Statistics Malaysia, in 2014 there were 760 thousand head of cattle in Malaysia. In addition, the potential for electricity generation from the manure of these cattle could be up to 100 Megawatt. However, the practice of generating electricity from animal manure is an uncommon practice in Malaysia and this study is designed to explore the reasons behind this situation. Objective: This study aims to identify the drivers and barriers that exist for biogas stakeholders in Malaysia in regard to the implementation of biogas-electricity projects. Results: The study identified several factors that can be considered as critical factors for the successful implementation of biogas-electricity projects in Malaysia. Conclusion: This study provides some new insights into biogas-electricity implementation for the cattle farming industry in Malaysia.